Dexamethasone intravitreal implant in serpiginous choroiditis. Issue 3 (2nd June 2016) - Miserocchi, Elisabetta; Berchicci, Luigi; Iuliano, Lorenzo; Modorati, Giulio; Bandello, Francesco
Abstract : Background/aims: To assess the efficacy and safety of dexamethasone (DEX) intravitreal implant in patients with active serpiginous choroiditis (SC) already receiving maximal tolerated systemic immunosuppressive therapy. Methods: In this retrospective longitudinal study we evaluated patients receiving 0.7 mg DEX intravitreal implant for active SC despite maximal systemic immunosuppression. Medical history was reviewed over a period of 18 months for each patient. We diagnosed SC activity using direct fundus examination and blue-light fundus autofluorescence. Primary outcomes were the rate of disease control and functional changes at end of follow-up. Secondary outcomes were the incidence of injection-related adverse events and the success of immunosuppression tapering at the last examination. Results: We examined eight eyes of seven patients. We controlled SC activity with one injection in five eyes, two injections in one eye, and three injections in two eyes (total of 13 implants). Best-corrected visual acuity at the end of the investigational period improved in two eyes (25%), remained stable in four eyes (50%) and decreased in two eyes (25%). Three eyes showed transient intraocular pressure increase and two eyes disclosed cataract progression. The average dosage of systemic prednisone at baseline and after DEX intravitreal implant decreased from 8.8 to 2.8 mg/day. Conclusions: Dexamethasone intravitreal implant may be an effective treatment option to control active serpiginous lesions in patients in whom increased systemic corticosteroid therapy is contraindicated.